Buhunuah Hill Tourism Supporting Capacity of Tunggul Boyok Village, Bonti Sub-District, Sanggau Regency - siahaan, sarma; Atma Sya'ban, Hendy; Widiastuti, Tri; Silvia Uthari Nuzaverra Mayang Mangurai (Journal of Sylva Indonesiana, 2025)
Buhunuah Hill is a tourist destination located in Petuo Hamlet, Tunggul Boyok Village, Bonti District, Sanggau Regency, West Kalimantan Province. This Buhunuah Hill tourist attraction is still relatively new, so there is a lack of information about the number of proper tourist capacities in the Buhunuah Hill camping area, which is not optimal. Therefore, it is necessary to conduct research on the Buhunuah Hill Tourism Carrying Capacity for its development. This study aims to obtain the value of the carrying capacity of the area, including physical carrying capacity, real carrying capacity, and effective carrying capacity. This study used survey, observation, and interview methods. The analysis used is quantitative descriptive analysis. This study shows that the physical carrying capacity (PCC) value of the camping area is 11, the real carrying capacity (RCC) value for Buhunuah Hill tourism is 11, and the effective carrying capacity (ECC) value for Buhunuah Hill tourism is 11. The carrying capacity value results are obtained by the equation PCC = RCC = ECC. This means that the carrying capacity value of Buhunuah Hill tourism is optimal and can accommodate tourists with all tourism activities as long as it does not exceed the maximum value of tourism carrying capacity.